Expression and Characterization of Recombinant Human Protein S in Heterologous Cells - Studies of the Interaction of Amino Acid Residues Leu-608 to Glu-612 with Human C4b-Binding Protein - Chang, Glenn T G; Ploos van Amstel, Hans K; Hessing, Martin; Reitsma, Pieter H; Bertina, Rogier M; Bouma, Bonno N (Thrombosis and Haemostasis, 1992)
Mouse C127 epithelioid cells were genetically engineered to produce biologically active ³-carboxylated human protein S. A full length human protein S cDNA was cloned into a bovine papilloma virus (BPV) based shuttle vector under the transcriptional control of the Moloney murine sarcoma virus enhancer and the mouse metallothionein promoter. Stable expression was obtained in transfected C127 cells. Expression of ³-carboxylated protein S was dependent on the presence of vitamin K in the culture medium. Protein sequence analysis showed that recombinant and plasma protein S have the same amino terminal sequence. Analysis of specific post-translationally modified amino acids shows that recombinant protein S is fully ³-carboxylated and fully p-hydroxylated. Immunoblotting analysis using polyclonal and monoclonal antibodies shows that recombinant protein S has a slightly higher molecular weight than plasma protein S. After N-Glycanase treatment, identical molecular weights are observed for recombinant and plasma protein S, indicating that the difference is caused by differences in the N-linked carbohydrate side chains. Recombinant protein S also demonstrates normal cofactor activity for activated protein C in a clotting assay. Binding studies with the complement component, C4b-binding protein (C4BP), shows that recombinant protein S binds to C4BP with the same apparent affinity as plasma protein S. Two variant molecules are also tested for their binding to C4BP. The first variant has a replacement of amino acid residue leu-608 by val and was designated B variant. The second variant has three alterations, at positions 609, 611 and 612 where the acidic amino acid residues asp, asp and glu were replaced by asn, asn and gin, respectively and this variant was designated C variant. The binding of these variants to C4BP was the same as wild type recombinant protein S. This suggests that amino acid residues leu-608, asp-609, asp-611 and glu-612 are not essential for binding of the intact full length protein to C4BP.